Sarcomas of the cervix uteri (a review of literature) - A. N. Gritsay; S. A. Shvachko; N. I. Lazareva; S. B. Peterson; A. P. Nikolayev (Опухоли женской репродуктивной системы)
The review of literature describes the etiology and clinical features of sarcomas of the cervix uteri and current approaches to their diagnosis and treatment.